User Experience Foundations - de Voil, Nick (BCS, The Chartered Institute for IT, 2020)
User experience (UX) is about how interaction with a product, service or system is perceived by its users. Are their needs met or exceeded? Do they enjoy the experience? Will they return? Making UX central to development of a product, service or system enhances customer satisfaction, resulting in higher conversion rates and a stronger brand presence. Applying the same techniques to internal business systems brings improved efficiency and job satisfaction.This book provides a reasoned and authoritative description of what UX is, why it works and what tools and techniques are involved, in line with the BCS Foundation Certificate in User Experience, based on ISO 9241-210.